2019 Investment Policy and Regulatory Review - Turkey - World Bank (World Bank, Washington, DC, 2020)
This Investment Policy and Regulatory Review (IPRR) presents information on the legal and regulatory frameworks governing foreign direct investment (FDI) and competition that affect businesses and foreign investors in Turkey. The research was primarily based on a review of currently applicable policies, laws and regulations. It is not a comprehensive review of the entire legal and regulatory framework affecting investment. Information presented is not exhaustive, but illustrative of the main topics and issues covered.